RUSSIA’S CHEMICAL AND PETROCHEMICAL INDUSTRIES AT THE EVE OF WTO-ACCESSION - Budzinski, Oliver; Schaimijeva, Elmira; Gumerova, Gjusel; Jasper, Jörg (Journal of Advanced Research in Law and Economics, 2017)
Although Russia’s WTO-accession is foreseeable, there are still deficits in the literature on its concrete effects on the sectoral and regional levels. In this paper we analyse effects on Russia’s chemical and petrochemical sectors (CPS), which are, unlike for example its oil and mineral gas industry, rarely in the focus of public attention. On the basis of an extensive examination of these sectors’ current condition, we expect serious problems for them to emerge in the nearer future, the perhaps most serious and most puzzling problem being under-investment. Our analysis is based on data provided by GOSKOMSTAT/ROSSTAT, Russia’s official statistics institute.
Keywords: Russia; chemical and petrochemical industries; WTO